Improved magnetostriction of Tb-Dy-Fe/Dy–Cu multilayer films by introducing interfacial stress due to the semi coherent interface - Yuze Zhao; Jiheng Li; Xiaoqian Bao; Xuexu Gao (Journal of Materials Research and Technology)
Magnetostrictive thin films are commonly applied in micro-electro-mechanical system (MEMS). Tb-Dy-Fe thin films have large magnetostrictive strain and high response frequency, which can efficiently realize the conversion of mechanical energy and electromagnetic energy, and are very suitable for application in MEMS. In this work, magnetostrictive Tb0.3Dy0.7Fe2 single-layer films and Tb0.3Dy0.7Fe2/Dy0.5Cu0.5 multilayers were prepared by direct-current (DC) magnetron sputtering. The effects of microstructure and interface stress on magnetic properties were investigated. The microstructure of as-deposited multilayer films showed clearly the high degree of layer periodicity. After the heat treatment of 475 °C for 1 h, the layers of Tb0.3Dy0.7Fe2 and Dy0.5Cu0.5 have undergone crystallization. The semi-coherent interface was obtained between Tb-Dy-Fe layer and Dy–Cu layer in multilayer films, resulting in the compressive stress in the magnetic Tb-Dy-Fe layers. Magnetically, the coercivity Hc of multilayer films increased obviously compared that of single layer film, and further increased with the number of layers in a multilayer film. The change of coercivity may be attributed to the stress state of films. Compared with the 642 ppm of Tb0.3Dy0.7Fe2 single layer film under the magnetic field of 4000 Oe, the magnetostrictive strain of the [Tb0.3Dy0.7Fe2(50 nm)/Dy0.5Cu0.5(50 nm)]10 multilayer film reached 835 ppm under the same magnetic field. The increase of magnetostrictive strain in Tb0.3Dy0.7Fe2/Dy0.5Cu0.5 multilayer films was attributed to the interface compressive stress to the Tb-Dy-Fe layer through the Dy–Cu layer. The analysis of stress and strain distribution at the interface showed that Dy–Cu phase produced a maximum tensile strain of 3.8 %, and Tb-Dy-Fe phase correspondingly subjected to a significant compressive stress. By tailoring the anisotropy and magnetic domain structure through internal interface stress, it is expected to become an effective way to control the magnetic properties of magnetic thin films.